Enhancement of Himalayan irregular stone masonry buildings for resilient seismic design - Khadka, Shyam Sundar; Acharya, Sabin; Acharya, Ayush; Veletzos, Marc J. (Frontiers in Built Environment, 2023)
In the Himalayan region of Nepal, stone masonry has been used for centuries as the primary building material for structures with or without mud mortar. In three distinct remote rural villages, a thorough structural survey of approximately 223 buildings was conducted with an emphasis on their structural irregularities. The thickness of masonry walls frequently varied between floors, which caused mass irregularities. Openings in the front wall of the buildings were not symmetrical in the vertical direction, which caused in-plane discontinuity. There were also out-of-plane offset irregularities due to the cross wall on the ground floor. These buildings were irregular in many aspects and were constructed without seismic considerations. This type of construction is more susceptible to earthquakes as a result of these irregularities. In this study, a thorough examination of a typical building was conducted using construction information obtained following the 2015 Gorkha earthquake. The database for each structural typology was prepared with an emphasis on construction practice to enhance the seismic design. The use of mud/cement mortar was extremely sparse, and the use of timber bands at various heights along the height of the masonry wall and an inappropriate connection between the wall and the roof were also negligible. The three main community-learned improvements following damage were the replacement of the gable wall with a metal sheet, the reduction of individual stone masonry homes to one story, and lighter construction on the upper stories of hotel buildings. Based on regional building techniques, non-linear finite models for typical and enhanced buildings were simulated. Due to the irregular stone units, construction variability, and constrained linear behavior, stone masonry with and without mud mortar presents difficulties in conducting a detailed numerical analysis. The development of these structures using mud/cement mortar and other regional materials, with careful attention to detail, was found to have significant potential as a seismically resilient building form.